2020
DOI: 10.1177/0047287520934874
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Roles of DMO’s Social Media Efforts and Information Richness on Customer Engagement: Empirical Analysis on Facebook Event Pages

Abstract: This study examines how destination marketing organization’s (DMO’s) social media posts and comments increase customer engagement and explores the moderating role of information richness in the smart tourism context. To test the proposed hypotheses, the current study employed social media analytics by analyzing unique panel data from 72 DMOs’ Facebook event pages. The research findings indicate that a DMO’s social media efforts (quantitative aspect) are positively associated with customer engagement and DMOs h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 108 publications
1
52
0
Order By: Relevance
“…Second, this study focuses on sustainability communication on Instagram. Given that social media platforms differ in richness and engagement (Lee et al , 2020), researchers should consider different social media platforms’ characteristics in understanding the communication effectiveness of SMIs.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this study focuses on sustainability communication on Instagram. Given that social media platforms differ in richness and engagement (Lee et al , 2020), researchers should consider different social media platforms’ characteristics in understanding the communication effectiveness of SMIs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this approach has been widely adopted in the travel and tourism literature to examine communication strategies (e.g., Kucukusta et al, 2019 ; Su et al, 2015 ). In recent years, aspects like communication efforts, content, format and tourist response have been the focus of a number of empirical studies ( Gálvez-Rodríguez et al, 2020 ; Lee et al, 2021 ). Moreover, the marketing literature has also used this framework to assess the information source—especially with regard to credibility ( Levy and Gvili, 2015 ).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Research on the policymakers' perspective, however, is very limited. Taking South Korea as an example, Lee et al (2021) found that the volume of policymakers' Facebook posts positively influences customer engagement on social media interaction. In addition, if the official content is rich, then the customers become willing to engage in the post.…”
Section: Research From the Policymakers' Perspectivementioning
confidence: 99%